STRATEGY TO INCREASE THE DIGITALIZATION CAPACITY OF HOMESTAY MANAGERS IN PANDANREJO TOURISM VILLAGE, INDONESIA - Gusti Agung, I Gusti Agung Wahyu Adrian; Edwin Adriansyah; Brantas; Jatmiko Edy Waluyo (Politeknik Pariwisata NHI Bandung, 2024)
This research aims to describe community problems in Pandanrejo Tourism Village in managing homestays and implementing community empowerment that can be carried out in development in the village. The data sources for this research are primary data and secondary data. Primary data from this research consists of interviews and observations, while secondary data comes from literature and electronic media studies. This research uses several data collection tools, including interview guides, checklists, and sound, image, or video recording equipment. Data analysis in this research uses an interactive model by Miles and Huberman along with data paraphrasing techniques by carrying out interactive qualitative data analysis activities that continue continuously until completion, until the data is saturated. The activities of this analysis model consist of data reduction, data presentation, drawing conclusions, and verification. The results of the analysis that has been carried out show that the digital literacy level of homestay managers is 75%, they have basic knowledge about the use of hardware and software, 90% of homestay managers have internet access with adequate speed, and 40% face limited financial resources to invest in equipment. Analysing this provides a clear picture of the challenges and the steps that can be taken to overcome these problems. Based on the data that has been analysed, it can be concluded that efforts to increase digital literacy, website development, online marketing strategies, and internet accessibility are important keys to strengthening the digitalization of homestay managers.